Inequalities in the receipt of healthcare practitioner counseling for adults after COVID-19 in southern Brazil - Juliana Quadros Santos Rocha; Rinelly Pazinato Dutra; Yohana Pereira Vieira; Suele Manjourany Silva Duro; Mirelle de Oliveira Saes (BMC, 2023)
Abstract Health counseling is a prevention and health promotion action, especially in the context of a pandemic, for both preventing disease and maintaining health. Inequalities may affect receipt of health counseling. The aim was to provide an overview of the prevalence of receiving counseling and to analyze income inequality in the receipt of health counseling. Methods: This was a cross-sectional telephone survey study with individuals aged 18 years or older with diagnosis of symptomatic COVID-19 using RT-PCR testing between December 2020 and March 2021. They were asked about receipt of health counseling. Inequalities were assessed using the Slope Index of Inequality (SII) and Concentration Index (CIX) measures. We used the Chi-square test to assess the distribution of outcomes according to income. Adjusted analyses were performed using Poisson regression with robust variance adjustment. Results: A total of 2919 individuals were interviewed. Low prevalence of health counseling by healthcare practitioner was found. Participants with higher incomes were 30% more likely to receive more counseling. Conclusions: These results serve as a basis for aggregating public health promotion policies, in addition to reinforcing health counseling as a multidisciplinary team mission to promote greater health equity.